A simple design of mechanically robust, recyclable, and biodegradable composite films with high thermal stability and fluorescent properties. (May 2021) - Li, Jiongjiong; Jiang, Shuaicheng; Zhou, Ying; Li, Xiaona; Shi, Sheldon Q.; Li, Jianzhang
Abstract: It remains a big challenge to fabricate biodegradable and recyclable soy protein (SP)-based composite films with great toughness, high strength, and large ductility. In this work, a facile strategy was proposed for preparing advanced SP-based films by simple solution casting of SP and hydroxyl and primary amine-containing hyperbranched polysiloxane (HPSA). The developed SP/HPSA2 film exhibited a high toughness of 17.63 MJ m −3 and a high tensile strength of 15.19 MPa, which was, respectively, 424.70% and 551.93% increase compared with that of the neat SP-based film. Additionally, the SP/HPSA2 film possessed a large strain at failure of 151.01%. The advanced mechanical properties can be interpreted by the toughening and reinforcing mechanism associated with the strain-induced deformation of HPSA as well as the multiple interfacial hydrogen-bonding interactions within the interphase. The composite films exhibited great recyclability due to the reversibility of non-covalent interactions confined in the matrix. Moreover, owing to the incorporation of the heat-resistant and fluorescent HPSA, the SP/HPSA films also possessed high thermal stability and great fluorescent properties. This work offers a simple methodology for the design of mechanically robust, recyclable, and biodegradable composite films, which have potential applications in the fabrication of high-performance, high-transparency, and anti-counterfeiting packaging materials. Highlights: Biodegradable composite films are fabricated by integrating HPSA and soy protein. Effective energy dissipation mechanism endows the composites with excellent mechanical robustness. The composites are recyclable due to the reversibility of dynamic hydrogen bonds. The composites possess high thermal stability and great fluorescent properties.